Meeting the global demand of sports safety - Timpka, Toomas (2018)
Sports and physical activity are transforming, and being transformed by, the societies in which they are practised. From the perspectives of both competitive and non-competitive sports, the complexity of their integration into today’s society has led to neither sports federations nor governments being able to manage the safety problem alone. In other words, these agencies, whilst promoting sport and physical activity, deliver policy and practices in an uncoordinated way that largely ignores the need for a concurrent overall policy for sports safety. This article reviews and analyses the possibility of developing an overall sports safety policy from a global viewpoint. Firstly, we describe the role of sports in today’s societies and the context within which much sport is delivered. We then discuss global issues related to injury prevention and safety in sports, with practical relevance to this important sector, including an analysis of critical policy issues necessary for the future development of the area and significant safety gains for all. We argue that there is a need to establish the sports injury problem as a critical component of general global health policy agendas, and to introduce sports safety as a mandatory component of all sustainable sports organizations. We conclude that the establishment of an explicit intersection between science and policy making is necessary for the future development of sports and the necessary safety gains required for all participants around the world. The Safe Sports International safety promotion programme is outlined as an example of an international organization active within this arena.